FULL-TIME POLICY IN EARLY YEARS ELEMENTARY EDUCATION IN RECIFE - Pereira, Sarah Porto da Paixão Barbosa (2024)
This article aimed to analyze the interpretation and translation processes of managers of four full-time early years schools in the city of Recife. Semi-structured interviews were carried out with: the managers of the four full-time early years schools; two technicians from the education department involved with municipal politics. We also analyzed the documents that guide this policy to understand the curricular design. To analyze the data, we used Discursive Textual Analysis (ATD). We anchored ourselves in the studies of Ball, Maguire and Braun (2016), to understand the process of action of policies in schools by the subjects who participate in them. Currently (2024), the municipality of Recife has four full-time primary schools, established by Ordinance No. 2103 of December 27, 2019. Three of these come from previous experiences (Medeiros, 2016, Melo, 2017). According to the results, it is possible to affirm that municipal management has invested in education throughout the education network, through resources and materials and building requalification of units. However, managers point out situations of privilege in EMTIs, such as the creation of specific work groups and events, with monitoring of the four units carried out by a specific Center within the secretariat, which makes monitoring more efficient at the expense of other units in the network . The four schools also participate in local and national assessments, which indicates a logic aligned with the NGP, in the search for efficiency and results.